Communication with physicians in hospital rounds: An interview with nurses. (September 2016) - Nedfors, Karin; Borg, Christel; Fagerström, Cecilia
A hospital round is a long tradition in which nurses and physicians communicate to develop an integrated plan of care together with the patient. There is insufficient knowledge of care professionals' experiences of communication during hospital rounds, particularly in surgical units, where the physician is frequently absent during daily care. Hence, the aim of this study was to describe nurses' experiences of communication with physicians during hospital rounds in a surgical unit. Nine qualitative unstructured interviews with nurses were conducted and analysed using Burnard's description of content analysis. 'An encounter involving opportunities for and challenges to teamwork' was found to be the predominant theme. The hospital round in a surgical unit is a short encounter that can be challenged by missing patient care goals, difficulties in transmitting messages and frustration over unshared information. Further studies are needed to overcome existing knowledge gaps about communication during hospital rounds.